Penzion Za Stavením - Falta, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Diplomová práce se zabývá zpracováním určité části projektové dokumentace pro provádění novostavby penzionu. Daný objekt je situován na rovinném pozemku v obci Provodov – Šonov, katastrální území Šeřeč, spadající do Královehradeckého kraje. Penzion splňuje předepsané regulativy daného území. Penzion je navržen jako čtyřpodlažní s jedním podzemním a třemi nadzemními podlažími. Celková kapacita penzionu je 61 ubytovaných osob. Konstrukční systém objektu je stěnový. Zdivo v podzemním podlaží je ze ztraceného bednění a v nadzemní části objektu z vápenopískových tvárnic. Objekt je zateplen deskami z minerálních vláken. Stropní konstrukce je navržena z předpjatých železobetonových panelů. Střecha je řešena jako jednoplášťová plochá.

This thesis deals with processing of a certain part of project documentation for making a new-build house of a guest house. The given object is situated in a flat field in a village Provodov-Šonov, cadastral land Šeřeč which belongs to the Královéhradecký region. The guest house meets the village’s requirements. The guest house is designed as a four-floor building with one underground and three over ground floors. The overall capacity of the guest house is 61 accommodated people. There is a wall construction system. The wall in the underground floor is made from concrete blocks and in the over ground part there are limestone-sand blocks. The object is isolated with desks from mineral fibre. The ceiling construction is designed from prestressed iron-concrete panels. The roof is laid out as flat.
Pension behind Stavení
Keywords: Penzion; novostavba; stavba pro ubytování; stěnový sytém; plochá střecha; dřevěná okna.; Guesthouse; new building; building for accommodation; wall construction; flat roof; wooden windows.